2005
DOI: 10.1007/s00018-004-4262-1
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin reuptake inhibitors and cardiovascular diseases: a platelet connection

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are a heterogeneous group of new antidepressants that cause a well documented acquired but reversible serotonin deficiency in blood platelets. Platelets are small, anucleate cells and are the only blood cells specialized in storing peripheral serotonin. Platelets are also an integral part of the hemostatic process that is initiated during pathologic thrombus formation in cardiovascular diseases. Serotonin release from platelets is important for functional hemosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 103 publications
1
45
1
2
Order By: Relevance
“…Furthermore, in vitro studies have shown that addition of ADP to normal platelets in the presence of SSRIs causes microaggregation and primary aggregation but no or very little dense granule release which leads to the formation of loose and disaggregating clots (Maurer-Spurej 2005).…”
Section: Pharmacology Of Ssris On Platelets and The Biological Plausimentioning
confidence: 99%
“…Furthermore, in vitro studies have shown that addition of ADP to normal platelets in the presence of SSRIs causes microaggregation and primary aggregation but no or very little dense granule release which leads to the formation of loose and disaggregating clots (Maurer-Spurej 2005).…”
Section: Pharmacology Of Ssris On Platelets and The Biological Plausimentioning
confidence: 99%
“…The uptake of 5-HT into neurons is very important for the clearance of the synaptic cleft, preventing firing rates and overstimulation of receptors [64]. This uptake and the later release are blocked upon treatment with SSRIs, such as fluvoxamine, fluoxetine, nortryptiline, citopram, and escitalopram [65]. The different SSRIs vary in kinetics being competitive and non-competitive inhibitors.…”
Section: Clinical Applications: Effects Of Selective Serotonin Reuptamentioning
confidence: 99%
“…7 Patients with depression also have lower rates of medication adherence, increased rates of substance abuse and smoking, and lower levels of physical activity, all of which may contribute to poor cardiac outcomes on top of the physiological effects. 8,9 Differential medical treatment may also be important: Patients with depression and other affective disorders may be less likely to receive cardiac catheterization in the setting of an acute MI, although findings are mixed. 10,11 Interestingly, despite the increased recognition of the relationship between depression and CVD, efforts to intervene thus far have been disappointing.…”
Section: Article See P 493mentioning
confidence: 99%